The Role of the Muhammadiyah Student Association in Students' Independent Character Establishment Muhammadiyah SMP 29 Sawangan, Depok City - Setiawati; Ridas Santa Ramadhan (East Asian Journal of Multidisciplinary Research, 2022)
The Muhammadiyah Student Association (IPM) is not only a forum for to channel the talents and creativity of students at school, but also serves as one of the character building, especially the character of independence in everyday students. This study aims to describe and know about the role of the Muhammadiyah Student Association in the formation of Independent character of students at SMP Muhammadiyah 29 Sawangan, Depok City. The research method uses a qualitative method with a Model The descriptive analysis carried out with the types of data collection are: Purposive Sampling or sampling intentionally. As for the source the data in this study is a person or people who have experience, knowledge and information that can be accounted for regarding the role of the Muhammadiyah Student Association (IPM) in the formation of independent character Students at SMP Muhammadiyah 29 Sawangan. Technique Data collection  was obtained by means of observation, interviews and documentation.